Nuclear Power Plants as Equivalents of Hydroelectric Reservoirs and Providers of Grid Stability: The Case of the Brazilian Electrical System - Ivo Leandro Dorileo; Welson Bassi; Danilo Ferreira de Souza (Energies, 2025)
In the current configuration of Brazil’s hydro-thermal-wind power system, hydroelectric reservoirs have progressively lost their long-term regulatory role due to inadequate planning, inefficient energy use, and reduced inflows. In the context of the energy transition and the incorporation of low-emission technologies into the generation mix, this study proposes expanding nuclear baseload capacity as a “regulatory thermal buffer” to mitigate hydrological uncertainty and strengthen grid stability. Using the São Francisco River basin as a case study, an equivalence factor is developed to relate nuclear energy output to stored hydropower reservoir volume. Results show that nuclear generation can help restore the multi-annual regulatory capacity of Brazil’s hydropower system and enhance the resilience of the National Interconnected System by contributing substantial inertia to an increasingly variable, renewable-based grid.